Development of a computed tomography perfusion protocol to support large animal resuscitation research. Issue 5 (November 2021) - Abdou, Hossam; Elansary, Noha; Poliner, David; Patel, Neerav; Edwards, Joseph; Richmond, Michael; Rasmussen, Todd; Ptak, Thomas; Scalea, Thomas M.; Morrison, Jonathan J.
Abstract : BACKGROUND: Adequate cerebral perfusion is crucial for a positive neurological outcome in trauma; however, it is difficult to characterize in the acute setting with noninvasive methods. Intra-arterial computed tomography perfusion may offer a solution. The aim of this study was to develop an intra-arterial computed tomography perfusion protocol for resuscitation research. METHODS: The study examined intra-arterial contrast administration for computed tomography perfusion (CTP) acquisition. It consisted of three phases: intra-arterial contrast dose finding, evaluation of reproducibility, and evaluation during hypotension. Blood pressure and laser Doppler flow data were collected. In phase 1, animals underwent CTPs using several intra-arterial contrast injection protocols. In phase 2, animals underwent two CTPs 7 hours apart using the 2.5 mL/s for 3-second protocol. In phase 3, animals underwent CTPs at several pressures following a computer-controlled bleed including euvolemia and at systolic pressures of 60, 40, and 20 mm Hg. Phase 1 CTPs were evaluated for contrast-to-noise ratio. In phase 2, CTPs were compared within each animal and with laser Doppler flow using linear regression. Phase 3 CTPs were graphed against systolic pressure and fitted with a nonlinear fit. RESULTS: The protocol using 2.5mL/s for 3 seconds was optimal, demonstrating a contrast-to-noise ratio of 40.1 and a superior arterial input function curve compared with the 1 mL/s bolus. Cerebral blood flow demonstrated high concordance between baseline and end of study CTPs (R 2 = 0.82, p < 0.001). Cerebral blood flow also compared moderately well against laser Doppler flow during 8 (R 2 = 0.53, p = 0.03); however, laser Doppler flow did not perform well during hypovolemia, and the favorable concordance was not maintained (R 2 = 0.45, p = 0.06). Cerebral blood flow was graphed against systolic blood pressure and fitted with a nonlinear fit (R 2 = 0.95, p = 0.003). CONCLUSION: Computed tomography perfusion using intra-arterial contrast injection may offer a novel alternative to traditional CTP protocols that could prove a useful additional tool in the setting of resuscitation research.